Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1007/s11746-005-1095-0
|View full text |Cite
|
Sign up to set email alerts
|

Rubber seed oil quality assessment and authentication

Abstract: Physicochemical and instrumental characterization of rubber (Hevea brasiliensis Müll. Arg.) seed oil (RSO) was carried out for the purposes of quality assessment, identification, and authentication. Properties such as color (Lovibond), specific gravity, percent FFA (as oleic acid), acid value, saponification value, iodine value, and viscosity were determined. FA composition and M.W. averages of RSO were determined using GLC and gel permeation chromatography (GPC), respectively. Structural features of RSO were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 14 publications
(19 reference statements)
1
18
0
Order By: Relevance
“…We found three major products: 1,3 -butadiene, 2 -methyl (1.68 min), limonene (14.48 min), and hexadecanoic acid (43.46 min); this last compound being a consequence of the thermal degradation of palmitic acid used as a lubricant. 12,13 We can also observe more than 10 peaks of lesser intensity, where different compounds derived from the thermal decomposition of the tire appear (Table II).…”
Section: Py-gc/ms Analyses Of Virgin Fiber and Tire Fibermentioning
confidence: 95%
“…We found three major products: 1,3 -butadiene, 2 -methyl (1.68 min), limonene (14.48 min), and hexadecanoic acid (43.46 min); this last compound being a consequence of the thermal degradation of palmitic acid used as a lubricant. 12,13 We can also observe more than 10 peaks of lesser intensity, where different compounds derived from the thermal decomposition of the tire appear (Table II).…”
Section: Py-gc/ms Analyses Of Virgin Fiber and Tire Fibermentioning
confidence: 95%
“…Aigbodion and Bakare [6] reported that rubber seed oil contains oleic acid (22.95%), linoleic acid (37.28%) and linolenic acid; also known as omega-3 (19.22%). Rubber seed oil contains alpha-linoleic acid which is one of the omega-3 fatty acids which is very important in our daily diet.…”
Section: Introductionmentioning
confidence: 99%
“…VVO with acetone extract values less than 20% is regarded as first grade, greater than 20% but less than 35% is medium grade, and greater than 35% as commercial grade (Reynolds, 1962). However, a higher acetone extract value does not necessarily imply that the VVO is inferior for a particular application; VVO is specifiable only by its actual performance in tests in rubber, and not by simple chemical tests alone (Nag et al, 1995) and Rubber seed oil (Aigbodion and Bakare, 2005 (Lower, 1984). Though VVO has been used for several years, only limited number of vegetable oils such as soybean oil, castor oil, rapeseed oil, crambe oil and linseed oil are used in its preparation (Erhan and Kleiman, 1990).…”
Section: Introductionmentioning
confidence: 99%